Maturation and Emigration of Single-Positive Thymocytes - Xi Xu; Shusong Zhang; Pingping Li; Jin Lu; Qun Xuan; Qing Ge (Clinical and Developmental Immunology)
T lymphopoiesis in the thymus was thought to be completed once it reaches the single positive (SP) stage, a stage when T cells are “fully mature” and waiting to be exported at random or follow a “first-in-first-out” manner. Recent evidence, however, has revealed that the newly generated SP thymocytes undergo a multistage maturation program in the thymic medulla. Such maturation is followed by a tightly regulated emigration process and a further postthymic maturation of recent thymic emigrants (RTEs). This review summarizes recent progress in the late stage T cell development. The regulation of this developmental process is discussed.